Assessment of the professional competences of doctors - Jańczyk, Magdalena; Samek, Ilona; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
Introduction: Competences are a combination of knowledge in a specific area, skills and attitudes. The professional group most often assessed in this regard are doctors. After leaving the office, patients assess the competences of a healthcare professional in relation to their own observations. Aim of the study: Presentation of the society’s assessment of physicians’ competences. Material and methods: The research was carried out using an original questionnaire. 210 questionnaires were collected and analyzed. Discussion of the results: Men (29%) and women (71%) participated in the study. The analysis showed that, according to a quarter of the respondents, doctors are not competent. Only 45.72% of people indicated positive feelings about the doctor’s appointment. The respondents expressed their opinion in a similar way regarding the lack of time regarding the survey (48.10%). Almost 40% of them did not show trust in the health care system, as opposed to trust in a specialist, which is not displayed by 13% of respondents. Conclusions: The data suggest that doctors in their work are assessed quite well by patients, especially specialist doctors. However, there is controversy over how the health service is to be delivered.